Simulation of Capacitively Coupled Dual-Frequency N2, O2, N2/O2 Discharges： Effects of External Parameters on Plasma Characteristics - 尤左伟 戴忠玲 王友年 (等离子体科学与技术：英文版, 2014)
A one-dimensional fluid model is adopted to simulate the characteristics of N2, O2, and N2/O2 dual-frequency （DF） capacitively coupled plasmas （CCPs） under typical conditions in PECVD technologies. Not only the ground, the excited states but also the vibration levels of the main species are considered. The study focuses on the influence of external parameters such as matching of the high-frequency （HF） and low-frequency （LF）, HF and LF of the voltage sources, as well as discharge pressures, on physical characteristics of discharges. The results show that the decoupling of the two sources is possible by increasing the applied HF, the electron density and ion flux are determined only by the HF of the voltage source, whereas the LF has a little influence on the plasma characteristics. In addition, the matching of frequency affects the characteristics of discharges to some extent. Fhrthermore, the pressure is a main external parameter affecting the characteristics of discharges, and a small amount of oxygen in N2 plasma can efficiently increase N＋ ion flux incident onto the electrode and the density of N atom.